Traditional versus scientific method: the differences exist between selecting players - Mohammed, Zerf; Abelatif, Houar; Mokhtar, Mime; Ali, Bengoua (Journal of Physical Education and Sport, 2016)
The purpose of this study was to evaluate the differences existed between the traditional method and Scientific, based on the Soccer Post-Game. Where our sample was the Selecting Players, representing the lightship Oran for year 2014- 2015. On this basis as specialists, our interventions have come to determine, firstly the errors of the traditional method, as well as differences between the post-game. Where our objective was to integrate the scientific observation as a means to analyse the data acquired by research Team, for the 38 players selected, tested by the test Cooper and vertical jump as physiological parameters, body fat and body mass index as anthropometric characteristics. Based on the analysis statistics, we confirm the defects of the traditional method: a) the weakness of the traditional method is in Body Fat Which cannot be predicted with the naked eye. b) All attackers and defenders chosen, have more body fat, at less maximal aerobic capacity and string. c) The difference between the selected players return to the relationships body fat with the performance demands physiological. On based on differences acquired by research Team, we subject that the tradition is not more subjective methods of selecting Algerian players. Thing confirmed in the participation of national young teams in various world championships and internal continent, which is not famous, observed in the choice of the national team coach, which prefers to recruit players from abroad and dispenses on the local player Service.